Залежність твердості та інших властивостей сірого чавуну від його вуглецевого еквівалента та ступеня евтектичності - Сіренко, К. А.; Мазур, В. Л.; Дереча, Д. О. (Physico-technological Institute of Metals and Alloys, 2023)
The chemical composition, carbon equivalent and properties of castings from unalloyed and low-alloyed gray irons with lamellar graphite of various grades from СЧ100 to СЧА400 were analyzed in accordance with DSTU 8833:2019. There is a reference to such cast iron in the technical conditions for brake pads made of composite materials (rubber mixtures), in particular, for the production of cast iron inserts. Other products for railway transport are also made from cast iron СЧ350, for example, the friction “Khanin wedge”. It is shown that in industrial batches of the “Khanin wedge”, cast from cast iron СЧ350, the hardness did not correlate either with the content of elements in the chemical composition of the cast iron, or with the carbon equivalent due to the narrow range of its values even within the cast iron of the same grade. According to DSTU 8833:2019, with an increase in the carbon equivalent in the possible regulated range of values (%) from 3.03 to 4.54, the Brinell hardness of HB monotonically decreases by approximately 1.54...1.57, and the coefficient of thermal conductivity increases by almost one and a half times. Reducing the sulfur content in the chemical composition from 0.20 to 0.05 % of CH350 cast iron significantly reduces the range of dispersion of the carbon equivalent. The parameters (mean values, mean square deviations and coefficients of variation) of the carbon equivalent and the degree of eutecticity of the chemical composition of cast irons with lamellar graphite of brands from СЧ100 to СЧА400 were determined by means of statistical tests using the Monte Carlo method. It is shown that due to the significant dispersion of the values of the carbon equivalent of the chemical composition, hardness, coefficient of thermal conductivity, strength, density, modulus of elasticity, linear shrinkage, heat capacity, coefficient of linear expansion of cast iron with lamellar graphite of grades from СЧ100 to СЧА400 according to DSTU 8833:2019, it is necessary from the specified list grades of cast iron to determine and regulate in the technical conditions for composite brake pads a specific grade of cast iron intended for the manufacture of inserts in such pads.